Analysis of Slang in the Film "Isi & Ossi" - Siregar, Vanessa Amanda (Asian Journal of Applied Education (AJAE), 2024)
The purpose of this study is to identify and analyze the language of slang in the film "Isi & Ossi" by Oliver Kienle. This paper is a literature study that uses a qualitative descriptive method with the help of the language characteristics of young people according to Helmut Henne. The data of this research is in the form of sentences taken from the subtitles of the film "Isi & Ossi" by Oliver Kienle. This research was conducted in the language laboratory of the Department of Foreign Languages, State University of Medan. Based on Henne's theory, 30 young people's slang were found in the film.